ICP-MS based metallomics and GC-MS based metabolomics reveals the physiological and metabolic responses of Dendrobium huoshanense plants exposed to Fe3O4 nanoparticles - Wang, Zhaojian; Wu, Jing; Sun, Zongping; Jiang, Weimin; Liu, Yingying; Tang, Jun; Meng, Xiaoxi; Su, Xinglong; Wu, Liping; Wang, Longhai; Guo, Xiaohu; Peng, Daiyin; et al. (Frontiers in Nutrition, 2022)
It is found that the growth of Dendrobium huoshanense was dependent on Fe3O4, while the bioavailability of plants to ordinary Fe3O4 was low on the earth. In order to improve the growth, quality and yield of D. huoshanense, we used Fe3O4 NPs (100 or 200 mg/L) that was easily absorbed by plants as nano-fertilizer to hydroponically treat seedlings of D. huoshanense for 3 weeks. Fe3O4 NPs induced not only earlier flowering and increased sugar content and photosynthesis, but also stressed to plants, increased MDA content and related antioxidant enzymes activities. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) revealed that Fe3O4 NPs caused a significant accumulation of Fe and some other nutrient elements (Mn, Co, B, Mo) in stems of D. huoshanense. Metabolomics revealed that the metabolites were reprogrammed in D. huoshanense when under Fe3O4 NPs exposure. Fe3O4 NPs inhibited antioxidant defense-related pathways, demonstrating that Fe3O4 NPs have antioxidant capacity to protect D. huoshanense from damage. As the first study associating Fe3O4 NPs with the quality of D. huoshanense, it provided vital insights into the molecular mechanisms of how D. huoshanense responds to Fe3O4 NPs, ensuring the reasonable use of Fe3O4 NPs as nano-fertilizer.